2019
DOI: 10.1021/acs.jmedchem.9b01112
|View full text |Cite
|
Sign up to set email alerts
|

2-Aminomethylene-5-sulfonylthiazole Inhibitors of Lysyl Oxidase (LOX) and LOXL2 Show Significant Efficacy in Delaying Tumor Growth

Abstract: The lysyl oxidase (LOX) family of extracellular proteins plays a vital role in catalyzing the formation of crosslinks in fibrillar elastin and collagens leading to extracellular matrix (ECM) stabilization. These enzymes have also been implicated in tumor progression and metastatic disease and have thus become an attractive therapeutic target for many types of invasive cancers. Following our recently published work on the discovery of aminomethylenethiophenes (AMTs) as potent, orally bioavailable LOX/LOXL2 inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Springer et al demonstrated that the LOX inhibitor CCT365623, bearing an aminomethylenethiophene (AMT) scaffold, has exhibited anti-metastasis efficacy in a LOX-driven spontaneous breast cancer model [ 98 ]. The team soon after suggested a series of 2-aminomethylene-5-sulfonylthiazole (AMTz) as dual inhibitors of LOX and LOXL2 [ 99 ]. One of the AMTz-bearing inhibitors, AMTz-21b, effectively suppressed tumor growth in their spontaneous breast cancer mouse model [ 99 ].…”
Section: Therapeutic Potential Of Targeting Approaches On Lox Famimentioning
confidence: 99%
See 1 more Smart Citation
“…Springer et al demonstrated that the LOX inhibitor CCT365623, bearing an aminomethylenethiophene (AMT) scaffold, has exhibited anti-metastasis efficacy in a LOX-driven spontaneous breast cancer model [ 98 ]. The team soon after suggested a series of 2-aminomethylene-5-sulfonylthiazole (AMTz) as dual inhibitors of LOX and LOXL2 [ 99 ]. One of the AMTz-bearing inhibitors, AMTz-21b, effectively suppressed tumor growth in their spontaneous breast cancer mouse model [ 99 ].…”
Section: Therapeutic Potential Of Targeting Approaches On Lox Famimentioning
confidence: 99%
“…The team soon after suggested a series of 2-aminomethylene-5-sulfonylthiazole (AMTz) as dual inhibitors of LOX and LOXL2 [ 99 ]. One of the AMTz-bearing inhibitors, AMTz-21b, effectively suppressed tumor growth in their spontaneous breast cancer mouse model [ 99 ]. Meanwhile, dextran sulfate (DS) acts to down-regulate the expression of LOX to suppress invasive and migratory behaviors in gastric cancer cells [ 100 ].…”
Section: Therapeutic Potential Of Targeting Approaches On Lox Famimentioning
confidence: 99%
“…In summary 21b, coupled with the improved PK profile and LOXL2 selectivity, demonstrated anti-tumor efficacy in a LOX-dependent genetically engineered mouse model (GEMM) breast cancer model. [139] The exemplar compound in Entry 5 (Table 3), was tested in a mouse model. It showed a reduction in cancer tongue volume and metastasis of cancer in oral metastatic cancer within a mice model.…”
Section: Next Generation Small Molecule Inhibitors Of Loxl2mentioning
confidence: 99%
“…The most established LOXL2 inhibitor is β-aminoproprionitrile (BAPN), which irreversibly inhibits the enzyme activity of LOXL2 (34). Recently, a subseries of LOXL2 specific inhibitors containing an aminomethiophene (AMT) scaffold were revealed to inhibit tumor growth (35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%